2009
DOI: 10.1007/s00253-009-2293-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid production is enhanced by the additional co-expression of UDP-glucose pyrophosphorylase in Lactococcus lactis

Abstract: Hyaluronic acid (HA) production was metabolically engineered in Lactococcus lactis by introducing the HA synthetic machinery from the has operon of the pathogenic bacterium Streptococcus zooepidemicus. This study shows that the insertion of uridine diphosphate (UDP)-glucose pyrophosphorylase (hasC) gene in addition to the HA synthase (hasA) and UDP-glucose dehydrogenase (hasB) genes has a significant impact on increasing HA production. The recombinant L. lactis NZ9000 strain transformed with the plasmid pSJR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 29 publications
3
59
0
2
Order By: Relevance
“…As expected, the highest production of heparosan was reached by the co-expression of KfiA, KfiB, KfiC and KfiD. The similar phenomenon was also observed for the production of hyaluronic acid by recombinant Lactococcus lactis, where it was found that the insertion of uridine diphosphate-glucose pyrophosphorylase gene in addition to the HA synthase and UDP-glucose dehydrogenase genes can significantly increase HA production (Prasad et al, 2010).…”
Section: Discussionsupporting
confidence: 62%
“…As expected, the highest production of heparosan was reached by the co-expression of KfiA, KfiB, KfiC and KfiD. The similar phenomenon was also observed for the production of hyaluronic acid by recombinant Lactococcus lactis, where it was found that the insertion of uridine diphosphate-glucose pyrophosphorylase gene in addition to the HA synthase and UDP-glucose dehydrogenase genes can significantly increase HA production (Prasad et al, 2010).…”
Section: Discussionsupporting
confidence: 62%
“…The engineered strain produced 0.5 g/L HA in shaker flask and 2.0-3.8 g/L HA in a fed-batch culture process in a 1-L bioreactor [45]. L. lactis was engineered by introducing the HA synthetic machinery from the has operon of S. zooepidemicus , and it was found that the insertion of uridine diphosphate-glucose pyrophosphorylase ( hasC ) gene in addition to the HA synthase ( hasA ) and UDP-glucose dehydrogenase ( has B ) genes can significantly increase HA production [46]. The recombinant L. lactis NZ9000 strain transformed with the plasmid pSJR3 (co-expressing hasA , hasB , and hasC genes) gave a maximum of 1.8 g/L HA in a 2.4-L batch bioreactor [46].…”
Section: Introductionmentioning
confidence: 99%
“…L. lactis was engineered by introducing the HA synthetic machinery from the has operon of S. zooepidemicus , and it was found that the insertion of uridine diphosphate-glucose pyrophosphorylase ( hasC ) gene in addition to the HA synthase ( hasA ) and UDP-glucose dehydrogenase ( has B ) genes can significantly increase HA production [46]. The recombinant L. lactis NZ9000 strain transformed with the plasmid pSJR3 (co-expressing hasA , hasB , and hasC genes) gave a maximum of 1.8 g/L HA in a 2.4-L batch bioreactor [46]. The hasA gene from S. zooepidemicus was expressed in B. subtilis for the production of HA, and it was found that the production of UDP-glucuronic acid is limiting in B. subtilis and that overexpressing the hasA gene along with the endogenous tuaD gene is sufficient for high-level production of HA in B. subtilis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Izawa et al (2010) reported that Streptococcus thermophilus YIT 2084, a GRAS strain isolated from a dairy food product, was able to produce HA from milk, although at a concentration lower than that achieved by S. equi. Recently, great effort has been put on the development of heterologous systems by transforming bacterial species that normally do not produce HA (e.g., Escherichia coli, Lactococcus lactis, or Bacillus subtilis) into HA producers (Mao et al 2009;Prasad et al 2010;Yamada and Kawasaki 2005;Yu and Stephanopoulos 2008;Widner et al 2005). However, there are restrictions to the use of recombinant strains in some countries and the production achieved by heterologous HA-producer systems, as well as the polymer's molecular weight, was considerably lower than those obtained by wild-type streptococcal fermentation.…”
Section: Bioactive Bacterial Polysaccharidesmentioning
confidence: 99%